2005
DOI: 10.1099/mic.0.27877-0
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy study on specificity and non-specificity of interaction forces between Enterococcus faecalis cells with and without aggregation substance

Abstract: Enterococcus faecalis is one of the leading causes of hospital-acquired infections, and indwelling medical devices are especially prone to infection. E. faecalis expressing aggregation substance (Agg) adheres to biomaterial surfaces by means of positive cooperativity, i.e. the ability of one adhering organism to stimulate adhesion of other organisms in its immediate vicinity. In this study, atomic force microscopy (AFM) was used to measure the specificity and non-specificity of interaction forces between E. fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
0
19
1
Order By: Relevance
“…The adhesion forces measured by AFM must therefore have been associated with nonspecific interactions and were Ϫ1.5 to Ϫ2.1 nN, which is two-to threefold less than the values obtained for the combined nonspecific and specific interactions between LT11 and laminin films. It is interesting that both similar ratios and similar absolute values for these interaction forces also occurred when workers compared specific and nonspecific interactions between (non)aggregating E. faecalis (41) and (non)coaggregating oral bacterial strains (35). The adhesion forces between a laminin-coated AFM tip and the streptococcal cell surfaces can also be compared with the forces measured in an analogous way for highly specific, irreversible ligand-receptor pairs.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The adhesion forces measured by AFM must therefore have been associated with nonspecific interactions and were Ϫ1.5 to Ϫ2.1 nN, which is two-to threefold less than the values obtained for the combined nonspecific and specific interactions between LT11 and laminin films. It is interesting that both similar ratios and similar absolute values for these interaction forces also occurred when workers compared specific and nonspecific interactions between (non)aggregating E. faecalis (41) and (non)coaggregating oral bacterial strains (35). The adhesion forces between a laminin-coated AFM tip and the streptococcal cell surfaces can also be compared with the forces measured in an analogous way for highly specific, irreversible ligand-receptor pairs.…”
Section: Discussionmentioning
confidence: 82%
“…Enterococcus faecalis strains expressing aggregation substance (Agg) and adhering to biomaterial surfaces by means of positive cooperativity exhibited interaction forces between bacterial cells (about Ϫ2.5 nN) that were nearly twofold greater than the forces observed for a strain lacking Agg (adhesive force, Ϫ1.3 nN). The strong interaction forces between the strains with Agg decreased after adsorption of antibodies against Agg to about Ϫ1.2 nN, demonstrating the influence of specific antibodies on interaction forces between E. faecalis strains (41). Thus, these experiments indicated that it was possible that AFM could be used to experimentally distinguish between specific and nonspecific force components.…”
mentioning
confidence: 73%
“…powerful tool that has proven useful in determining intraspecies adhesion forces (Dufrêne, 2002;Postollec et al, 2006;Waar et al, 2005). Based on these measurements, deletion of als3 demonstrated a significant reduction in the staphylococcal-hyphal binding force (Fig.…”
Section: Silvermanmentioning
confidence: 99%
“…Long-range interactions are nonspecific interactions and act at a distance greater than 50 nm. These interactions are a function of the distance and free energy (Waar et al 2005). Three types of forces make up the long-range attractive interactions between polar molecules: the induction force, the orientation force, and the dispersion force (Liang et al 2007).…”
Section: Physical and Chemical Properties Of Surfacesmentioning
confidence: 99%